Prevalence of Lesions and oral mucosal normal variations in an elderly populationin Costa Rica = Prevalencia de lesiones y variaciones de lo normal en la mucosa oral en una población de adultos mayores de Costa Rica - Fernández Chaves, José Manuel 1979-; Boza Oreamuno, Yadira Vanessa 1974-; Masís Monestel, Carlos 1977-; Lau Sánchez, Norma Celina 1952- (2024)
To establish the prevalence of oral mucosal lesions and normal variations in a population of older adults. This observational study was conducted from 2015 to 2016 and involved 156 participants from Los Guido (San José, Costa Rica). The participants' sociodemographic information, risk factors, comorbidity, and clinical examination were evaluated and analyzed descriptively and qualitatively. Findings in oral mucosa were found to preferentially affect women (n=111; 71%) and individuals between the ages of 60 and 69 years (n=65; 42%), having smoking as a risk factor (n=67; 43%), and suffering from arterial hypertension (n=101; 65%). Intraoral findings were mainly presented together with variations from normal and pathology (n=71; 46%), predominantly one variation from normal (n=67; 33%) and one pathology (n=51; 43%). The most prevalent normal variations were the saburral tongue, lingual varicose veins, and cryptic tonsils. Infectious diseases (n=33; 21%), potentially malignant disorders (n=30; 19%), and physical and chemical injuries (n=18; 12%) were the most prevalent groups. The four most predominant lesions were prosthetic stomatitis, actinic cheilitis, frictional keratosis, and atrophic glossitis. The differences in pathological groups were not statistically significant (p=0.392) when comparing the frequency ratio by sex. Variations of the normal anatomy are the predominant ones, the saburral tongue being the most prevalent individually; among the pathologies, the most remarkable group was the infectious diseases, and prosthetic stomatitis was the most frequent. The information about this subject in Costa Rica is limited. So it is important to conduct more studies that contribute to the oral health of the elderly population in this area.
Establecer la prevalencia de lesiones de la mucosa oral y variaciones de lo normal en una población de adultos mayores. Estudio observacional en 156 participantes de Los Guido (San José, Costa Rica) del 2015 a 2016. Se evaluaron y analizaron de forma descriptiva y cualitativa información sociodemográfica, factores de riesgo, comorbilidad y exploración clínica. Los hallazgos en mucosa oral afectaron preferentemente a las mujeres (n=111; 71%), el rango de edad entre 60 y 69 años (n=65; 42%) y con el tabaco como factor de riesgo (n=67; 43%) e hipertensión arterial (n=101; 65%). Los hallazgos intraorales se presentaron preferentemente de forma conjunta variaciones de lo normal y patologías (n=71; 46%), predominantemente una variación de lo normal (n=67; 33%) y una patología (n=51; 43%). Las variaciones de lo normal más prevalentes fueron lengua saburral, várices linguales y amígdalas criptodónticas. Las enfermedades infecciosas (n=33; 21%), los desórdenes potencialmente malignos (n=30; 19 %) e injurias físicas y químicas (n=18; 12%) fueron los grupos más prevalentes. Las cuatro lesiones más predominantes fueron estomatitis protésica, queilitis actínica, queratosis friccional y glositis atrófica. No hubo diferencia estadísticamente significativa (p=0.392) al comparar la proporción de frecuencia por sexo. Las variaciones de la anatomía normal predominaron; siendo en forma individual la lengua saburral la más frecuente; de las patologías destacaron las enfermedades infecciosas principalmente la estomatitis protésica. Existe poca información en esta área en Costa Rica, es importante generar más estudios que permitan contribuir con la salud oral de la población adulta mayor.
En revista Odóvtos, vol. 26, no.2 (mayo-agosto 2024)
Descripción basada en el contenido visto el 04 de febrero, 2025
También disponible en formato HTML y EPUB